Scalable preconditioning of block-structured linear algebra systems using ADMM. (2nd February 2020) - Rodriguez, Jose S.; Laird, Carl D.; Zavala, Victor M.
Highlights: Propose ADMM to precondition the iterative Krylov solver GMRES. Approach overcomes scalability limits of Schur complement decomposition. Use approach to solve problems arising in power networks with millions of variables. Abstract: We study the solution of block-structured linear algebra systems arising in optimization by using iterative solution techniques. These systems are the core computational bottleneck of many problems of interest such as parameter estimation, optimal control, network optimization, and stochastic programming. Our approach uses a Krylov solver (GMRES) that is preconditioned with an alternating method of multipliers (ADMM). We show that this ADMM-GMRES approach overcomes well-known scalability issues of Schur complement decomposition in problems that exhibit a high degree of coupling. The effectiveness of the approach is demonstrated using linear systems that arise in stochastic optimal power flow problems and that contain up to 2 million total variables and 4000 coupling variables. We find that ADMM-GMRES is nearly an order of magnitude faster than Schur complement decomposition. Moreover, we demonstrate that the approach is robust to the selection of the augmented Lagrangian penalty parameter, which is a key advantage over the direct use of ADMM.